2023
DOI: 10.1371/journal.pone.0274657
|View full text |Cite
|
Sign up to set email alerts
|

Trends of cleft surgeries and predictors of late primary surgery among children with cleft lip and palate at the University College Hospital, Nigeria: A retrospective cohort study

Abstract: Background Cleft of the lip and palate is the most common craniofacial birth defect with a worldwide incidence of one in 700 live births. Early surgical repairs are aimed at improving appearance, speech, hearing, psychosocial development and avoiding impediments to social integration. Many interventions including the Smile Train partner model have been introduced to identify and perform prompt surgical procedures for the affected babies. However, little is known about the trends of the incidence and surgical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Figure 4 compares the proportion of delayed primary cleft surgeries among countries based on previous studies. 6,7,18 Regarding delayed primary lip surgery beyond 6 months of age, this study revealed the highest contribution to surgical delay (65.3%). In terms of delayed primary palatal repair beyond 18 months of age, the results from Indonesia (67%) were comparable to those of the Nigerian study (67.1%).…”
Section: Comparison Of Timeliness At Primary Surgery Between Countriesmentioning
confidence: 74%
See 2 more Smart Citations
“…Figure 4 compares the proportion of delayed primary cleft surgeries among countries based on previous studies. 6,7,18 Regarding delayed primary lip surgery beyond 6 months of age, this study revealed the highest contribution to surgical delay (65.3%). In terms of delayed primary palatal repair beyond 18 months of age, the results from Indonesia (67%) were comparable to those of the Nigerian study (67.1%).…”
Section: Comparison Of Timeliness At Primary Surgery Between Countriesmentioning
confidence: 74%
“…Previous studies within the 5 years time-frame have explored the STX database to gain insight of OFC in multiple LMIC settings, 13,[23][24][25][26] or single LMIC settings such as Nigeria. 6 These studies have demonstrated the significant role of a humanitarian organization in enhancing access to care for those in need while also increasing research volume for treatment outcome and epidemiology fields. Indonesian population that would otherwise be challenging to study.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This rec ommendation is based on the findings of our research. Abd El-Ghafour, 2020 14 16 Nigeria retrospective cohort study…”
Section: Patient With Clpmentioning
confidence: 99%
“…The intraoperative and early postoperative complications associated with cleft lip and palate were assessed. 15 Michael, et al (2023) 16 conduected a study with 314 cleft surgery. The mean age of the patients was 58.08 ± 99.65 months.…”
Section: Cleft Surgeriesmentioning
confidence: 99%